2021
DOI: 10.1101/2021.02.11.430724
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Feedforward ribosome control mitigates gene activation burden

Abstract: Overexpression of synthetic genes depletes cellular resources, particularly ribosomes, which leads to lower expression of other synthetic genes and decreased growth rate. These burden effects can be detrimental to genetic circuit performance and hinders the process of modularly composing genetic circuits to create complex biomolecular systems with novel functions. No solution exists that allows the expression of any gene to a desired level without hindering the expression level of all other genes and growth r… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 114 publications
(343 reference statements)
0
6
0
Order By: Relevance
“…In turn, the operation of genetic devices can change the cell's growth rate (Ceroni et al, 2015;Jones et al, 2020). One way to approach the problem of genetic devices affecting cell growth rates has been to use feedforward and/or feedback controllers to limit the burden of genetic devices on the bacterial (Barajas et al, 2021;Ceroni et al, 2018) or mammalian cell (Lillacci et al, 2018) (Figures 9Aii and 9Cii), thus better optimizing the resource usage of a genetic device given the constraints of the cellular environment. Note that the (Huang et al, 2018).…”
Section: Applications Of Controllers To Insulate Genetic Device Function From Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…In turn, the operation of genetic devices can change the cell's growth rate (Ceroni et al, 2015;Jones et al, 2020). One way to approach the problem of genetic devices affecting cell growth rates has been to use feedforward and/or feedback controllers to limit the burden of genetic devices on the bacterial (Barajas et al, 2021;Ceroni et al, 2018) or mammalian cell (Lillacci et al, 2018) (Figures 9Aii and 9Cii), thus better optimizing the resource usage of a genetic device given the constraints of the cellular environment. Note that the (Huang et al, 2018).…”
Section: Applications Of Controllers To Insulate Genetic Device Function From Contextmentioning
confidence: 99%
“…These designs have also enabled adaptation to DNA copy number (Bleris et al, 2011;Jones et al, 2020;Lillacci et al, 2018), as well as resource competition (Frei et al, 2020a;Jones et al, 2020), transcriptional inducers (Strovas et al, 2014), and changes in protease production (Gao et al, 2018). (Cv) A recent study demonstrated feedforward control of ribosome levels to offset loading of the ribosome by the output protein by co-expressing SpoTH, the hydrolysis domain of SpoT, a positive regulator of ribosome activity in bacteria (Barajas et al, 2021). This was shown to reduce the effects of resource loading both on other genes and on cell growth rates.…”
Section: Applications Of Controllers To Insulate Genetic Device Function From Contextmentioning
confidence: 99%
“…Barajas et al utilized a similar global architecture of circuit-wide activation (rather than repression) by coexpressing the hydrolysis domain of SpoTH to upregulate free ribosome production with the gene of interest, resulting in sufficient resources to overcome the increased resource load of the gene of interest. 27 In the LC archetype, on the other hand, each controller node represses only the gene it is regulating. Jones et al also demonstrated the efficacy of this controller type by coexpressing an endoribonuclease along with the gene-of-interest, which targets the mRNA of gene-of-interest, thereby mitigating the resource consumption of the gene-of-interest via a local feedforward control mechanism.…”
Section: ■ Resultsmentioning
confidence: 99%
“…Incoherent feedforward loops (iFFLs) couple both activation and repression arms and have been implicated to function in adaptation behavior and pulse generation. They have also been demonstrated to function as resource regulators due to the repressive links inherent to the iFFL architecture, much like the negative feedback motif. Here, we extend our analysis of the aforementioned three controller architectures to iFFLs.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding of how circuits integrate into the native cellular context is important for preventing circuit retroactivity within the model and within the circuit. Circuit retroactivity, where the system does not function as intended due to coupling to other systems within the cell or to the specific cell states, represents a notable challenge to robust circuit design [95,102,103]. Similarly, examples from introduction of synthetic effectors of the RNAi pathway indicate that synthetic components can sequester resources and systemically alter cellular behavior [104][105][106].…”
Section: Trends In Biotechnologymentioning
confidence: 99%